2021
DOI: 10.3390/s21020549
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Fault Diagnosis of Hydraulic Piston Pump Based on Wavelet Analysis and Improved AlexNet

Abstract: Hydraulic piston pump is the heart of hydraulic transmission system. On account of the limitations of traditional fault diagnosis in the dependence on expert experience knowledge and the extraction of fault features, it is of great meaning to explore the intelligent diagnosis methods of hydraulic piston pump. Motivated by deep learning theory, a novel intelligent fault diagnosis method for hydraulic piston pump is proposed via combining wavelet analysis with improved convolutional neural network (CNN). Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 42 publications
(50 reference statements)
0
38
0
Order By: Relevance
“…A more comprehensive comparison between 1DCNN and MC1DCNN has been made in the results of this paper, so the 1DCNN model of the literature [ 25 , 26 ] is not compared subsequently. The models selected for comparison are the VMD-ELM model of the literature [ 15 ], the MVMD-SVM model of the literature [ 17 ], and the VMD-CNN model of the literature [ 22 ]. Since both the VMD-ELM model and the MVMD-SVM model require feature extraction of the vibration signal, in the process of performing MWPE feature extraction, we found that the larger embedding dimension and scale factor of the Multiscale Weighted Permutation Entropy (MWPE) algorithm increase the computing time significantly, so the CNN model has an absolute advantage in diagnostic time after training is completed.…”
Section: Experiments and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A more comprehensive comparison between 1DCNN and MC1DCNN has been made in the results of this paper, so the 1DCNN model of the literature [ 25 , 26 ] is not compared subsequently. The models selected for comparison are the VMD-ELM model of the literature [ 15 ], the MVMD-SVM model of the literature [ 17 ], and the VMD-CNN model of the literature [ 22 ]. Since both the VMD-ELM model and the MVMD-SVM model require feature extraction of the vibration signal, in the process of performing MWPE feature extraction, we found that the larger embedding dimension and scale factor of the Multiscale Weighted Permutation Entropy (MWPE) algorithm increase the computing time significantly, so the CNN model has an absolute advantage in diagnostic time after training is completed.…”
Section: Experiments and Results Analysismentioning
confidence: 99%
“…On the other hand, vibration data can be transformed into image formats such as grayscale images, frequency domain maps and speech spectrum maps for recognition. In [ 22 ], Zhu transformed the signal by short-time Fourier transform into a frequency domain map for fault diagnosis by CNN. In [ 23 ], Zhao transformed the one-dimensional vibration signal into a two-dimensional grayscale image and achieved diagnostic classification of faults by CNN.…”
Section: Introductionmentioning
confidence: 99%
“…In the orthogonal experiment analysis, although the range analysis is simple, the effect of the experimental error on the results cannot be excluded, and the accuracy of the analysis cannot be verified. Therefore, the F function should be used to conduct variance analysis for each factor and the interaction between factors, further excluding the experimental error and exploring the effect of each factor on the index [40,41]. The F function is as follows:…”
Section: Variance Analysis Of the Orthogonal Experimentsmentioning
confidence: 99%
“…According to the literature [37], approximately 20% of all damages in hydraulic systems are pump damages, which are the key elements of the system. Due to the importance of this element, more effective methods of diagnosing them are in the interests of many researchers in the world [38][39][40]. One of the most popular types of hydraulic pumps is a variable displacement axial piston pump.…”
Section: Introductionmentioning
confidence: 99%